2011
DOI: 10.1038/leu.2011.231
|View full text |Cite
|
Sign up to set email alerts
|

Release of intracellular calcium primes chronic myeloid leukaemia cells for tyrosine kinase inhibitor-induced apoptosis

Abstract: Imatinib is a substrate for hOCT1 (SLC22A1) and inhibitors of this influx transporter, such as amantadine and prazosin, have previously been shown to decrease cellular imatinib uptake. However, here we report that in longer term experiments, both drugs paradoxically increase the cytotoxicity of all three currently licensed tyrosine kinase inhibitors (TKIs), imatinib, nilotinib and dasatinib. This effect is due to release of intracellular calcium from the endoplasmic reticulum (ER), with changes in mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Phosphorylation of Bcr-Abl is known to induce proliferation and apoptosis resistance. 24–26 However, phosphorylation of Bcr-Abl was significantly downregulated after 5–15 min of incubation with isononyl alcohol ( Figure 5b ). After 30 min of incubation, Bcr-Abl phosphorylation returned to basal levels.…”
Section: Resultsmentioning
confidence: 95%
“…Phosphorylation of Bcr-Abl is known to induce proliferation and apoptosis resistance. 24–26 However, phosphorylation of Bcr-Abl was significantly downregulated after 5–15 min of incubation with isononyl alcohol ( Figure 5b ). After 30 min of incubation, Bcr-Abl phosphorylation returned to basal levels.…”
Section: Resultsmentioning
confidence: 95%
“…43 However, ER stress appears more likely to impair than to promote macrophage differentiation. 44 Our findings suggest that the differentiation-promoting effects of amantandine may depend on its ability to induce an increase in the expression of VDR.…”
Section: Discussionmentioning
confidence: 99%
“…Also Gromicho et al [43] suggested that effective uptake of dasatinib is not likely to occur with the help of hOCT1. Forchap et al [47] concluded that dasatinib is not primarily transported by hOCT1.…”
Section: Discussionmentioning
confidence: 99%